<span>3x + (x-8) = 23
Combine like terms first. You can combine 3x and x because they have the same variable.
4x - 8 = 23
Now add 8 to both sides.
4x = 31
Last step is to divide both sides by 4 to isolate the x.
4/4x = 31/4
x = 7.75 is the answer.</span>
Answer:
3N + 10
Step-by-step explanation:
Answer:
try b
Step-by-step explanation:
Answer:
(A) ![e^2](https://tex.z-dn.net/?f=e%5E2)
(b) ![e^{-3}](https://tex.z-dn.net/?f=e%5E%7B-3%7D)
(c) ![e^2](https://tex.z-dn.net/?f=e%5E2)
(d) ![e^3](https://tex.z-dn.net/?f=e%5E3)
Step-by-step explanation:
We have given expression and we have to simplify the expression using exponent property
(A) ![(\frac{1}{e})^{-2}](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7Be%7D%29%5E%7B-2%7D)
So ![(\frac{1}{e})^{-2}=\frac{1}{e^{-2}}=e^2](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7Be%7D%29%5E%7B-2%7D%3D%5Cfrac%7B1%7D%7Be%5E%7B-2%7D%7D%3De%5E2)
(b) ![(\frac{e^5}{e^2})^{-1}](https://tex.z-dn.net/?f=%28%5Cfrac%7Be%5E5%7D%7Be%5E2%7D%29%5E%7B-1%7D)
So ![(\frac{e^5}{e^2})^{-1}=(e^{3})^{-1}=e^{-3}](https://tex.z-dn.net/?f=%28%5Cfrac%7Be%5E5%7D%7Be%5E2%7D%29%5E%7B-1%7D%3D%28e%5E%7B3%7D%29%5E%7B-1%7D%3De%5E%7B-3%7D)
(c) ![\frac{e^5}{e^3}](https://tex.z-dn.net/?f=%5Cfrac%7Be%5E5%7D%7Be%5E3%7D)
So ![\frac{e^5}{e^3}=e^2](https://tex.z-dn.net/?f=%5Cfrac%7Be%5E5%7D%7Be%5E3%7D%3De%5E2)
(d) ![\frac{1}{e^{-3}}=e^3](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Be%5E%7B-3%7D%7D%3De%5E3)
Answer:
x = 107
Step-by-step explanation:
44+29+107=180
a triangle equals 180 with all the degrees added together :)